Penerapan Algoritma K-Means Dalam Clustering Data Seleksi Benih Kelapa Sawit Di PPKS Unit Marihat - Tambunan, Fazli Nugraha (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Oil palm is one of the most useful gardens in daily life. In addition to producing vegetable oil, oil palm seeds can also be marketed. In this study, palm oil seed data will be clustered using the K-Means method to determine the results of good seeds. Clustering means a method of analyzing data whose purpose is to group data with the same characteristics and characteristics in an area. While K-Means is a data analysis method or Data Mining method that performs unsupervised modeling process and is one of the methods that classify data with a partition system (division of an object into several parts with a specific purpose). The K-Means method seeks to group existing data into several groups, where data in one group has similar characteristics to each other and has different characteristics from data in other groups. In other words, this method tries to minimize the variation between data in a cluster and maximize the variation with data in other clusters.